Berufliche Weiterbildung in Großbritannien für gering qualifizierte Arbeitskräfte - Peter Schröter (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
Die Aktivitäten im Bereich der beruflichen Weiterbildung erreichen innerhalb des deutschen Beschäftigungssystems lediglich ein unterdurchschnittliches Niveau. Der stetige Anstieg der Qualifikationsanforderungen erfordert jedoch eine Steigerung der Weiterbildungsaktivitäten und insbesondere eine Bildungsstrategie, die vor allem niedrig qualifizierte Arbeitskräfte aktiviert und in lebensbegleitende Lernprozesse integriert. Die Studie macht deutlich, dass ein simultaner Einsatz unterschiedlicher Instrumente die Weiterbildungsteilnahme von gering Qualifizierten signifikant erhöhen kann. Gegenüber einer pauschalen Förderung von Weiterbildungsaktivitäten kann die zunehmende Zielgruppenorientierung in der britischen Weiterbildungspolitik zur Effizienzsteigerung staatlicher Steuerungsprozesse als vorbildhaft eingestuft werden. – – In the German employment system only a low level of activity in continuing vocational training is notable. However, the steady increase of qualification needs has to lead to a training strategy in which particularly the low-skilled will obtain instruments which support the processes of lifelong learning. This study examines the institutional framework and the specific training instruments of the continuing education system in United Kingdom, in order to show successful solutions in this field. Because of the weakness of the initial vocational training system, a system immanent constraint in the British employment system can be found which supports subsequent qualification activities of the labour force during the lifetime. Therefore, there have been large experiences with a wide spectrum of training instruments on the national level. Concerning the question of directing training activities, the study will analyze both employee-led and employer-led instruments. These instruments are intended to influence five parts of the continuing training process: Informational networks to prepare an activity; monetary incentives to start an activity; rules of training leave of employees; the modular education system and finally, specific mentoring structures for employees and employers. This discussion paper will show that several innovative arrangements have been implemented within the British training system. This study will show that a simultaneous adoption of different instruments would be able to lead to a significant increase in the participation of low-skilled in continuing training. Compared to a training promotion for everyone, the stronger focus on specific target groups within the British training policy can be categorised as an exemplary approach in order to increase the efficiency of governance.
Keywords: 330